Unravelling the risks of construction digitalisation in developing countries. Issue 3 (24th June 2021) - Aghimien, Douglas; Aigbavboa, Clinton; Meno, Tsholofelo; Ikuabe, Matthew
Abstract : Purpose: This study aims to present the result of an assessment of the risk of construction digitalisation with a view to sensitising and preparing construction organisations for unforeseen issues that might arise in the course of their digital transformation. Design/methodology/approach: The study took a post-positivist stance through a quantitative research approach. A survey of construction professionals actively involved in construction projects in South Africa was conducted using a structured questionnaire. The analysis of the data gathered was done using mean item scores, Kruskal–Wallis H test, exploratory factor analysis (EFA) and structural equation modelling (SEM). Findings: EFA revealed five principal risk factors (human and financial, technological, legal and security, operations and socioeconomic risk factors) associated with the digitalisation of construction organisations. However, SEM revealed that four out of these risk components have significant direct relationships with some selected digitalisation outcomes. These significant risk factors are technology, legal and security issues, operations and socioeconomic issues. Originality/value: This study provides practical insight into the risk inherent in construction digitalisation, and its result can help organisations seeking to be digitally transformed make informed decisions. Theoretically, the study reveals the risks associated with construction digitalisation – an aspect that has not gained significant attention in the current fourth industrial revolution discourse. Therefore, its findings can form a basis for future studies on the risk of digitalising construction organisations.